Primary anaplastic large cell lymphoma of the CNS as initial presentation of HIV infection: A case report - Carolina Strosberg; Elizabeth M. Sagatys (Elsevier, 2021)
Primary anaplastic large cell lymphoma (ALCL) of the central nervous system (CNS) is a rare entity. Most primary CNS lymphomas are of B-cell origin, including those associated with HIV. We report a case of a 29-year-old woman who presented with worsening headaches and was subsequently diagnosed with primary anaplastic large cell lymphoma, ALK positive of the CNS. On further workup, she was also diagnosed with HIV. This is the first reported case of primary anaplastic large cell lymphoma, ALK positive of the CNS in an HIV-positive individual.